Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula - Vicente, Carlos San (Zootaxa, 2017)
The zoogeographic distribution of mysid species occurring in the diverse seas of the Iberian Peninsula and neighbouring areas is analysed. For each species, bathymetric range and localities data are reported. A total of 129 mysid species belonging to 50 genera have been recorded, representing 11% of all known world extant species and the 28% of genera. Littoral mysids are the most diverse group (64 species) followed by the outer-self to upper-bathyal slope with 54 known species. Patterns of bathymetric zonation are characterized by four bathymetric discontinuities at about 100, 500, 1300 and 2700 m. Each geographical region is characterized by the presence of a mixture of exclusive and shared species composition. Mysid distributions suggest that an important grouping of species present in the Iberian fauna share a common origin. Based on the analysis of published records and reported species, it is suggested that there is a high probability of the discovery of new species of Mysida in the water surrounding the Iberian Peninsula.